Climate law and developing countries legal and policy challenges for the world economy (Cheltenham Edward Elgar, 2009)
This timely book examines the legal and policy challenges in international, regional and national settings, faced by developing countries in mitigating and adapting to climate change. With contributions from over 20 international scholars from developing and developed countries, the book tackles both long-standing concerns and current controversies. It considers the positions of developing countries in the negotiation of a new international legal regime to replace the Kyoto Protocol and canvasses various domestic issues, including implementation of CDM projects, governance of adaptation measures and regulation of the biofuels industry. Through a unique focus on the developing world, this book makes a significant contribution to understanding current challenges and future directions of climate law. It will prove a stimulating read for legal academics, undergraduate and graduate law students as well as policymakers interested in the role of developing countries in climate change law. The book originates from an international conference on Climate Law in Developing Countries Post-2012, co-sponsored by the IUCN Academy of Environmental Law, the University of Ottawa Faculty of Law and Osgoode Hall Law School. The book is part of the ongoing mandate of the IUCN Academy of Environmental Law to generate collaborative research on the most pressing issues in environmental law.
Includes bibliographic references and index
Keywords: Climatic changes --Law and legislation --Developing countries